Medicinal and Aromatic Plants in the North-West of Tunisia : Findings from a Value Chain and Jobs Survey - Weber, Michael; Salhab, Jade; Sanchez-Quintela, Sonia; Tsatsimpe, Keratilwe (World Bank, Washington, DC, 2020)
This report describes the findings of the value chain and jobs survey on the Medicinal and Aromatic Plants ("MAPs") in the North West of Tunisia. The survey also benchmarks the value chain against other leading countries in the MAPs industry to determine potential productivity gaps and areas for improvements to ultimately increase the sectors' competitiveness and create more and better jobs. This report is part of the "Value Chain Development for Jobs in Lagging Regions - Let's Work Program in Tunisia" which aims to identify some of the most binding constraints affecting the creation and productivity of jobs within targeted value chains in a lagging region in Tunisia and inform relevant World Bank Group lending projects currently in preparation to help tackle these constraints.